2006
DOI: 10.1111/j.1601-0825.2005.01217.x
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of oral mucosal pH values in healthy saliva secretors

Abstract: This method is easy and relatively quick to manipulate, and may offer many diagnostic possibilities for oral related diseases and disorders such as oral malodour, mouth breathing, dysgeusia, acidic diet consumption and gastrointestinal disorders affecting the mouth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
113
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(123 citation statements)
references
References 19 publications
6
113
0
4
Order By: Relevance
“…Although the positioning of the tape on the back of the tongue [16] can represent a study limitation, as the values measured at this location are higher than those found if the measurement was performed in the saliva [17], the results of this study confirm the significant reduction in the pH of the oral environment after ingestion of this soft drink, which may lead to losses in the mineral balance of the dental structure immediately after consumption.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Although the positioning of the tape on the back of the tongue [16] can represent a study limitation, as the values measured at this location are higher than those found if the measurement was performed in the saliva [17], the results of this study confirm the significant reduction in the pH of the oral environment after ingestion of this soft drink, which may lead to losses in the mineral balance of the dental structure immediately after consumption.…”
Section: Discussionsupporting
confidence: 72%
“…Based on predetermined exclusion criteria (physical limitation that prevented the examination, medication user and baseline salivary pH), seven children were excluded by presenting initial salivary pH (detected only after the first measurement) below 6.8 [17], resulting a total sample of 45 students (n = 45), 26 females and 19 males.…”
Section: Thismentioning
confidence: 99%
“…(i) We assume that the combination of neutral pH, hemin, and no CO 2 , which gives the shortest branching time (Figures 2 and 4), is a suitable model of the oral cavity [20], where bleeding occurs frequently as a result of a wide spectrum of pathological conditions [3,58,59]. It is important to note that hemin is released by oxidized ferric (Fe 3+ ) hemoglobin in the human body [60], and hemin has been demonstrated to initiate the Y → H morphological transition of C. albicans in vitro [13,14], which is likely to facilitate the superficial invasion of the oral mucosa by C. albicans in vivo [50,61,62].…”
Section: Discussionmentioning
confidence: 99%
“…albicans is able to colonize mucosa as a pathogenic fungus in a wide range of pH and CO 2 values [16,19]. For example, the mucosal pH in the oral cavity varies between 6.28 ± 0.36 (buccal mucosa) and 7.34 ± 0.38 (palate) with a mean value of 6.78 [20]. Meanwhile, the gastrointestinal tract shows wide differences in pH considering values reported for the stomach (extremely acidic like pH 2.0) and the intestine (pH~6.0-8.0) [16,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Kod nižih vrijednosti pH, primjerice kod pH = 6,9 (pH u mišićnim stanicama) 27 i 6,3 (pH sluznice usne šupljine), 28 kao u prethodnom slučaju, vrsta koja dominira je SO 4 2− (više od 99,99 %), dok je udjel HSO 4 − vrlo malen i on iznosi približno 0,001 % za pH = 6,9, a oko 0,005 % za pH = 6,3.…”
unclassified